Biomechanical study on the muscles' specific abilities of takeoff in long jump - Kun, W.; Wenyi, W. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Through using the method of biomechanical theory and experimental research, the paper studied the specific ability characteristics of takeoff leg muscles in long jump. Seven male long jumpers were required to complete running long jump. Kinematics and dynamics data were from biomechanical investigation. The 'Inverse Dynamics' method was used to calculate the muscles moment of hip, knee and ankle of the takeoff leg. The result showed that the ability of quick eccentric contraction of hip was important in takeoff. The knee was shown the characteristics of 'fore-support push' in take off. The ability of concentric contraction of knee's extensors played a very important part in getting vertical velocity, the larger peak of knee flexion moment emerged in earlier takeoff phase that indicated the knee flexion muscles actively contracted in this period.